PEMAHAMAN MASYARAKAT TENTANG PRODUK DAN OPERASIONAL PERBANKAN SYARIâAH DI PAMEKASAN - —, Sakinah (STAIN PAMEKASAN, 2011)
Understanding of Society about SyariâAh Banking still is minimum or less adequate. This matter is certainly influenced by some factors. This research aims to know the understanding of society about product and oprasional of SyariâAh Banking in Pamekasan chosening location of Perumnas of Tlanakan Indah, village of Asem Manis, Countryside of Larangan Tokol, District Of Tlanakan, Sub- Province of Pamekasan. Result of research indicates that ( 1) Understanding of society perumnas of Tlnakan Indah about product and operational of SyariâAh Banking is still very minimum. ( 2) Factors which influence caused some factors, for example, lack of information of side syariâah banking and lack of understanding of society about religion teaching especially which touch with muamalah covered in SyariâAh Banking.